BiP and Multiple DNAJ Molecular Chaperones in the Endoplasmic Reticulum Are Required for Efficient Simian Virus 40 Infection - Edward C. Goodwin; Alex Lipovsky; Takamasa Inoue; Thomas G. Magaldi; Anne P. B. Edwards; Kristin E. Y. Van Goor; Adrienne W. Paton; James C. Paton; Walter J. Atwood; Billy Tsai; Daniel DiMaio (mBio, 2011)
ABSTRACT Simian virus 40 (SV40) is a nonenveloped DNA virus that traffics through the endoplasmic reticulum (ER) en route to the nucleus, but the mechanisms of capsid disassembly and ER exit are poorly understood. We conducted an unbiased RNA interference screen to identify cellular genes required for SV40 infection. SV40 infection was specifically inhibited by up to 50-fold by knockdown of four different DNAJ molecular cochaperones or by inhibition of BiP, the Hsp70 partner of DNAJB11. These proteins were not required for the initiation of capsid disassembly, but knockdown markedly inhibited SV40 exit from the ER. In addition, BiP formed a complex with SV40 capsids in the ER in a DNAJB11-dependent fashion. These experiments identify five new cellular proteins required for SV40 infection and suggest that the binding of BiP to the capsid is required for ER exit. Further studies of these proteins will provide insight into the molecular mechanisms of polyomavirus infection and ER function. IMPORTANCE The polyomaviruses, including simian virus 40 (SV40), are important human pathogens and model systems for exploring the general features of virus replication and cell biology. We used a genetic system to interrogate the role of cellular genes in SV40 infection. Based on the results of this unbiased genetic screen and analysis of proteins related to the strongest hit from the screen, we identified five new cellular proteins required for the entry of SV40 into cells. These proteins physically associate with SV40 in the endoplasmic reticulum (ER) during virus entry and are required for exit of the partially disassembled virus from this organelle. These results demonstrate that the polyomaviruses have coopted an ER-localized protein quality control process to initiate disassembly and transit through the cell on their way to the nuclear site of virus replication.